2021
DOI: 10.14283/jpad.2021.2
|View full text |Cite
|
Sign up to set email alerts
|

Digital Screening for Cognitive Impairment – A Proof of Concept Study

Abstract: Background: Due to an ageing demographic and rapid increase of cognitive impairment and dementia, combined with potential disease-modifying drugs and other interventions in the pipeline, there is a need for the development of accurate, accessible and efficient cognitive screening instruments, focused on early-stage detection of neurodegenerative disorders. Objective: In this proof of concept report, we examine the validity of a newly developed digital cognitive test, the Geras Solutions Cognitive Test (GCST) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…Findings from our study showed that the DCS performed at least as well as other previous digital cognitive screening tools. For example, two recently developed digital cognitive tests which took more than 10 min to administrate showed AUCs of 0.87 and 0.91, respectively, for discriminating between demented and cognitively intact participants (10,24) while the AUC of that in our study was 0.95. Moreover, the DCS can provide several additional advantages.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Findings from our study showed that the DCS performed at least as well as other previous digital cognitive screening tools. For example, two recently developed digital cognitive tests which took more than 10 min to administrate showed AUCs of 0.87 and 0.91, respectively, for discriminating between demented and cognitively intact participants (10,24) while the AUC of that in our study was 0.95. Moreover, the DCS can provide several additional advantages.…”
Section: Discussioncontrasting
confidence: 44%
“…However, most of the presently available cognitive tests are touch screen-based, which requires operation from individual participant. This has resulted in lower test acceptance and performance due to computer illiteracy among older adults who are less familiar with operating digital devices (10,11). Furthermore, even though mobile platforms can collect new data streams and achieve a high measurement accuracy, they are usually expensive to track longitudinal behavioral/cognitive changes, such as sensor data through wearables (12, 13).…”
Section: Introductionmentioning
confidence: 99%
“…Tech companies have been showing a growing interest toward the generation of “smart” devices for physiological monitoring and assessment of cognitive functions, both heavily affected in dementia-related disorders. The emerging technologies that hold great promise in the prognosis of neurodegenerative disorders cover a wide spectrum of applications, ranging from the development of wearable devices, such as fitness trackers, smartwatches, and mobile apps, to artificial intelligence platforms, VR, and game-based systems, purposely designed for early diagnosing, monitoring and treating dementia symptoms (Zygouris et al, 2017 ; Mandryk and Birk, 2019 ; Piau et al, 2019 ; Bloniecki et al, 2021 ; Gielis et al, 2021 ; Majnarić et al, 2021 ). Overall, digital tools provide a constant and extensive amount of data reflecting an individual’s health status.…”
Section: New Technologies For Early Detection and Prevention Of Dementiamentioning
confidence: 99%
“…Beyond that, several user interfaces have been recently implemented to administer basic cognitive tests-such as the Montreal Cognitive Assessment (MoCA; Nasreddine et al, 2005 ), one of the most common screening methods used for the detection of MCI and AD, and normally conducted using “pen and paper”—in a computerized version that showed promising results to date (Berg et al, 2018 ). Another example indicating the expansion and contribution of new appliances in monitoring brain health is given by Bloniecki and coworkers, who developed a novel digital test to assess cognitive performance and validated its accuracy against the MoCA test (Bloniecki et al, 2021 ). These short examinations are reliable in distinguishing individuals with advanced cognitive impairment, but unable to detect earlier stages of deficit and insufficient to quantify subtle subjective cognitive complaints.…”
Section: New Technologies For Early Detection and Prevention Of Dementiamentioning
confidence: 99%
See 1 more Smart Citation